Funnel based reventure attribution of online canpaigns - Flaks, V.L. (Математичне моделювання в економіці, 2016)
The article reviews the problems of static attribution models of online stores transactions and suggests a solution in the form of dynamic attribution model based on customer behavior while customer journey on a website.